Application of tea polyphenols in combination with 6-gingerol on shrimp paste of during storage: biogenic amines formation and quality determination - Li, Jianrong (Frontiers in Microbiology, 2015)
Tea polyphenols (TP) have shown antioxidant activity and antimicrobial properties in the food industry. Assessment of anti-oxidation potential of 6-gingerol (GR) has also been verified. As little is known about the use of tea polyphenols either individually or in combination with 6-gingerol in shrimp paste, we aimed to investigate the effect of tea polyphenols combined with 6-gingerol on the biogenic amines inhibition and quality of shrimp paste stored at 25 °C for 160 days. The shrimp paste samples were assigned into four groups: (1) control; (2) tea polyphenols treatment (0.3%); (3) 6-gingerol treatment (0.3%); (4) tea polyphenols (0.15%) + 6-gingerol (0.15%). Samples with no addition were used as control. The results indicate that treatment with tea polyphenols + 6-gingerol (TPGR) maintained paste appearance, inhibited oxidation of protein and lipids, and reduced microorganism counts compared to control treatment. The efficiency was superior to that of tea polyphenols or 6-gingerol treatment. Furthermore, shrimp paste treated with TPGR also exhibited significantly higher inhibition of biogenic amines. Total amino acids determination proved the efficacy of TPGR by maintaining the more amino acids of shrimp paste during ambient temperature storage. Our study suggests that TPGR might be a promising candidate for fermented foods due to its synergistic effect to maintain products quality and extending their shelf-life.